A Review of Polycystic Ovarian Syndrome In Ayurveda - Rathee, Pallvi; Rathee, Satender (International Research Journal of Ayurveda & Yoga, 2022)
Polycystic ovarian syndrome is a heterogenous endocrine disorder & the most common growing health hazard amongst women of reproductive age. It is a combination of – Hyperandrogenism (clinical or biochemical), Oligomenorrhoea /or anovulation & polycystic ovaries. It is a frequently associated with insulin Resistance & Obesity. Basically, it is a systemic endocrine & metabolic disorder. Many Women with PCOS will give a history of infrequent cycles and skin manifestations include, acne, hirsutism, alopecia, obesity & Acanthosis Nigricans. In Ayurveda few diseases like Yoni Vyapad, Puspghani Jataharini, Nashtartav & Aartavadushti have some similarities with this disease. The particular or an exact disorder is not explained in Ayurveda. It involves imbalance of Dosha, Dhatu and Updhatu means different factors at different levels are involved in it. So the possible line of treatment is with by following Dincharya & Ritucharya , Nidaan Parivarjana, Samshodhana Aaganeya & Artavajanan Dravyas.So This paper is approach to explore ayurvedic concept of PCOS